ECOPRINT TRAINING AS AN INNOVATION IN INCREASING THE CREATIVITY OF WACHID HASYIM ELEMENTARY SCHOOL STUDENTS IN THE CITY OF SURABAYA - Harya, Gyska Indah; Mardika, Anggita; Sisyawati, Raniasani; Fahruddin, Khabib; Prasetyo, Rachmad Dwi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Art education often receives less attention than other academic fields. Art is an activity that can increase creativity and become a means of self-expression for students. Based on these conditions, students strive to raise awareness of art in elementary school students by holding training on making Batik Ecoprint using Tote Bag media. Ecoprinting is a technique for printing batik motifs using natural materials without chemicals such as leaves, flowers, and plants. Ecoprinting activities are included in art activities because they require creativity in doing so. This training activity is one of the activities of KKN-T Defending the Country of UPN "Veteran" East Java Students. The target of this activity is elementary school students in Grades 5A and 5B of Wachid Hasyim 2 Elementary School Surabaya. The results of the activity showed that 80% of SD Wachid Hasyim students were able to increase creativity, be able to understand the ecoprint process using natural materials and increase students awareness of the importance of protecting the environment. The skills of students who can explore art in eco-print batik design provide business opportunities for students to awaken the entrepreneurial spirit from an early age through their independent works.